Epsin15 Homology Domains: Role in the Pathogenesis of Pulmonary Arterial Hypertension - Predescu, Dan; Qin, Shanshan; Patel, Monal; Bardita, Cristina; Bhalli, Rabia; Predescu, Sanda (Frontiers in Physiology, 2018)
Intersectin-1s (ITSN) deficiency and expression of a biologically active ITSN fragment, result of granzyme B cleavage under inflammatory conditions associated with pulmonary arterial hypertension (PAH), are characteristics of lung tissue of human and animal models of PAH. Recently, we have shown that this ITSN fragment comprising two Epsin15 homology domains (EHITSN) triggers endothelial cell (EC) proliferation and the plexiform arteriopathy in PAH. Limited evidence also indicates that the EH domains of endocytic proteins such as ITSN, upregulate compensatory endocytic pathways in cells with impaired vesicular trafficking. Thus, we sought to investigate whether the EHITSN may be involved in this compensatory mechanism for improving the EC endocytic dysfunction induced by ITSN deficiency and possibly contribute to PAH pathogenesis. We used stably-transfected human pulmonary artery ECs expressing the Myc-EHITSN (ECEH-ITSN) and ITSN knockout heterozygous mice (K0ITSN+/-) transduced with the Myc-EHITSN, in conjunction with functional assays: the biotin assay for caveolae internalization and 8 nm gold (Au)- and dinitrophenylated (DNP)-albumin perfusion of murine lung microvasculature. Pulmonary artery ECs of PAH patients (ECPAH), ITSN knockdown ECs (ECKD-ITSN), the monocrotaline (MCT)-induced mouse and rat models of PAH, as well as untreated animals, served as controls. ELISA via streptavidin-HRP or anti-DNP antibody (Ab), applied on ECs and lung lysates indicated greater than 30% increase in biotin internalization in ECEH-ITSN compared to ECCtrl. Despite their endocytic deficiency, ECPAH internalized biotin similar to ECCtrl which is twofold higher compared to ECKD-ITSN. Moreover, the lung microvascular bed of Myc-EHITSN-transduced mice and MCT-treated animals showed greater than twofold increase in DNP-BSA transendothelial transport, all compared to untreated controls. Electron microscopy (EM) revealed the increased occurrence of non-conventional endocytic/transcytotic structures (i.e., caveolae clusters, tubulo-vesicular and enlarged endocytic structures, membranous rings), usually underrepresented. Most of these structures were labeled by Au-BSA, consistent with their involvement in the transendothelial transport. Furthermore, ITSN deficiency and EHITSN expression alter the subcellular localization of the EH-binding protein 1 (EHBP1) and cortical actin organization, altogether supporting the increase occurrence/trafficking of the alternative endocytic structures. Thus, the EHITSN by shifting the physiological vesicular (caveolae) transport toward the alternative endocytic pathways is a significant contributor to the dysfunctional molecular phenotype of ECPAH.